2022
DOI: 10.3390/jcm11051315
|View full text |Cite
|
Sign up to set email alerts
|

The Perceptions of Telehealth Physiotherapy for People with Bronchiectasis during a Global Pandemic—A Qualitative Study

Abstract: Physiotherapy is a core component of management for people with bronchiectasis and has predominantly been delivered in an in-person consultative format. With the global pandemic, a telehealth physiotherapy model of service evolved, but the perceptions and experiences from the consumer perspective of this service have not been evaluated. Participants who had a diagnosis of bronchiectasis and received a minimum of two telehealth physiotherapy sessions during the months of March 2020 to December 2020 at a private… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 45 publications
0
2
0
Order By: Relevance
“…In this study, most patients indicated greater interest in follow-up for physiotherapy using telephone compared with video consultation and app-based platforms, likely due to high familiarity with this method and potential lack of confidence with other forms of technology (13). Patient-provider communication through telephone has been used previously for information, advice, reassurance or monitoring purposes in respiratory patient populations (5) Most physiotherapy respondents indicated that they would be open to using video call methods for follow-up.…”
Section: Discussionmentioning
confidence: 88%
“…In this study, most patients indicated greater interest in follow-up for physiotherapy using telephone compared with video consultation and app-based platforms, likely due to high familiarity with this method and potential lack of confidence with other forms of technology (13). Patient-provider communication through telephone has been used previously for information, advice, reassurance or monitoring purposes in respiratory patient populations (5) Most physiotherapy respondents indicated that they would be open to using video call methods for follow-up.…”
Section: Discussionmentioning
confidence: 88%
“…Remote assessment is particularly challenging for physiotherapy, in which physical communication and touch have a key role. Lee and colleagues assessed a telehealth model of physiotherapy with prospective follow-up using semi-structured interviews [ 14 ]. This study only included nine participants with overall mixed opinions of the benefit of this intervention compared to traditional face-to-face interaction.…”
mentioning
confidence: 99%